2019
DOI: 10.5812/archcid.84764
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis and Integron Carriage of Mupirocin-Resistant Staphylococcus aureus Strains Isolated from Burn Wound Infections, Tehran, Iran

Abstract: Background:The prevalence of wound infections associated with multidrug-resistant Staphylococcus aureus (S. aureus) strains among burns patients has tremendously increased. Recently, the role of integrons as a key system involved in spreading multi-drug resistance has been well documented. Objectives: To investigate the prevalence of integrons, antimicrobial resistance pattern, and S. aureus protein A (spa) typing of the mupirocin-resistant S. aureus (MRSA) strains obtained from a referral burns hospital in Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In another, the study conducted in Egypt that detected mupirocin-resistant isolates from wound postoperatively found 38.5% of MRSA showed LLMR [40]. Also in Navidinia et al [41] study in Iran showed that 40 (62.5%) isolates were categorized as having low-level Mupirocin resistance. Mupirocin resistance is of significant concern for infection prevention strategies increasing bacterial resistance requires the discovery of new antimicrobial treatments [18].…”
Section: Discussionmentioning
confidence: 93%
“…In another, the study conducted in Egypt that detected mupirocin-resistant isolates from wound postoperatively found 38.5% of MRSA showed LLMR [40]. Also in Navidinia et al [41] study in Iran showed that 40 (62.5%) isolates were categorized as having low-level Mupirocin resistance. Mupirocin resistance is of significant concern for infection prevention strategies increasing bacterial resistance requires the discovery of new antimicrobial treatments [18].…”
Section: Discussionmentioning
confidence: 93%
“…A variety of micro-organisms can be associated with skin and soft tissue infections, Staphylococcus aureus being the commonest isolate. 1,2 b-lactam group of antibiotics is the most commonly used antibiotic for the treatment of Staphylococcus aureus infections. 3,4 However, Methicillin-resistant S. aureus (MRSA) poses severe therapeutic challenges.…”
Section: Introductionmentioning
confidence: 99%